ダイ52ジ ニホン ナンキョク チイキ カンソクタイ カキ コウドウ ホウコク 2010-2011 - 山内, 恭; ヤマノウチ, タカシ; Yamanouchi, Takashi (2011)
P(論文) 第52次日本南極地域観測隊は「南極地域観測第VIII期6か年計画」の初年度の計画を実行する隊として,観測実施計画及び設営計画は多岐にわたった.長期的に継続する定常観測,モニタリング観測から構成される基本観測を進めるとともに,新しく重点研究観測「南極域から探る地球温暖化」の下,三つのサブテーマ「南極中層・超高層大気を通して探る地球環境変動」,「南極域生態系応答を通して探る地球環境変動」及び「氷期-間氷期サイクルから見た現在と将来の地球環境」を開始し,さらに天文観測を含む一般研究観測10課題を実施した.大型大気レーダーの設置及び自然エネルギー棟建設という二つの大型建設計画を含め,物資輸送,昭和基地での作業,「しらせ」船上やドームふじ基地までの内陸旅行を含む沿岸野外での観測等,様々な課題を伴う夏期行動実施計画であった. 前次隊から続くリュツォ・ホルム湾の厳しい海氷状況などから,計画の完全実施は困難が予想された.実際,海氷状況及び天候は極めて厳しかった.定着氷が厚く,積雪も多く,さらに流氷域も広くかつ乱氷状態にあり,往路,復路共に大いに難渋した.また,12月中は比較的好天であったものの,1月に入るとほとんど毎日強風と降雪,吹雪の連続で,天候が悪いことも特徴であった.しかし,その中で大部分の夏期作業は進展し,大規模な作業はほぼ達成できた.2月中旬以降,強風と吹雪,さらにはブリザードにも襲われ,夏期間最終局面では飛行計画の遅れやアムンゼン湾オペレーションの中止等,変更を余儀なくされた. 一方,別働隊である東京海洋大学の研究練習船「海鷹丸」による観測も,海域は異なるものの厳しい海氷状況は同様であった.重点研究計画サブテーマ2を中心に,一般研究観測や東京海洋大学独自の計画を含め,観測が行われた. This report describes the activities of the 52nd Japanese Antarctic Research Expedition (JARE-52) during the 2010-2011 austral summer. JARE-52, as the first year of the"VIIIth JARE 6-year program", carried out various research projects and logistical plans. Basic observations, composed of routine observations and monitoring observations, were continued as part of long-term observations, and a newly established prioritized research program"Global Warming Investigated from the Antarctic"was started, comprising three sub-targets:"Global Environmental Changes from the Antarctic Middle and Upper Atmosphere","Responses of Southern Ocean Ecosystems in Global Warming"and"Current and Future Global Environment seen from Glacial-Interglacial Cycles". Ten projects of the ordinary research observations program, including astronomy in Antarctica, were also carried out. The largest tasks of the expedition were the setting of the large atmospheric MST/IS radar (PANSY) and the construction of a building for harnessing natural energy and providing garage space. The main summer activities involved the transportation of materials, the maintenance of facilities at Syowa Station, and observations from on board the icebreaker RV Shirase and in the field, including an inland trip to Dome ...